2019
DOI: 10.1186/s12916-019-1258-0
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after inpatient treatment for diarrhea in children: a cohort study

Abstract: BackgroundThere is an increasing recognition that children remain at elevated risk of death following discharge from health facilities in resource-poor settings. Diarrhea has previously been highlighted as a risk factor for post-discharge mortality.MethodsA retrospective cohort study was conducted to estimate the incidence and demographic, clinical, and biochemical features associated with inpatient and 1-year post-discharge mortality amongst children aged 2–59 months admitted with diarrhea from 2007 to 2015 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
(30 reference statements)
1
27
0
Order By: Relevance
“…Firstly, the majority of the children who were eligible to be in this study and died did not have a sample collected to determine their RVA and other enteric pathogens’ status. Secondly, inpatient mortality of children treated for diarrhea in Kilifi County Hospital has been previously found to be predicted by a positive HIV test, bacteremia and poor nutritional status [ 21 ]. This may have not changed pre- or post-introduction of rotavirus vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the majority of the children who were eligible to be in this study and died did not have a sample collected to determine their RVA and other enteric pathogens’ status. Secondly, inpatient mortality of children treated for diarrhea in Kilifi County Hospital has been previously found to be predicted by a positive HIV test, bacteremia and poor nutritional status [ 21 ]. This may have not changed pre- or post-introduction of rotavirus vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable Development Goal target 3.2 (<25 child deaths per 1000 live births by 2030) requires accelerated progress and attention to vulnerable populations [ 2 ]. Evidence from Kenya and other LMICs have identified the period following hospital discharge as a particularly high-risk period, in which children are often readmitted and experience a fatality rate eight-times higher than similarly-aged community peers [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In uncomplicated SAM, the mortality rate is < 5% while it varies from 10 to 40% in complicated SAM [ 6 ]. Further, previous reports have shown high post-discharge mortality following in-hospital management of diarrhea-SAM, HIV infection-SAM and pneumonia-SAM comorbidities respectively [ 7 9 ]. The FuSAM (Follow Up of Severely Acute Malnourished Children) study reported a mortality rate of 25% over a year after the SAM treatment among children followed in inpatient-based SAM treatment centre in Blantyre (Malawi).…”
Section: Introductionmentioning
confidence: 99%